Effectiveness of Early Childhood Obesity Prevention Programs in Primary Care Setting - Sarwar, Benash; Mujeeb ur Rahman; Gul, Sarooj (Indus Journal of Bioscience Research, 2025)
Background: Preventive infrastructure in low and middle income countries continue to be limited and childhood obesity is an escalating global health concern. The early childhood period is a critical period for establishing lifelong dietary and activity patterns as it presents an opportune window for intervention. The goal of this study was to test a structured obesity prevention program in the context of the primary care setting at Allied Hospital Faisalabad. Methods: The study is a prospective interventional one conducted from July to December, 2024, among 120 children aged 2–5 years. The participants were randomly assigned into intervention (n=60) and control (n=60) groups. Structured counseling on nutrition, physical activity, screen time reduction and sleep hygiene was provided to the intervention group during the routine visits, along with relevant educational materials and monthly follow ups. Standard pediatric care was given to the control group. Data were collected at baseline, 3 months and 6 months on anthropometric and behavioral measures. Results: After 6 months, the intervention group significantly decreased BMI percentile (BMIPCT: –5.7 ± 1.9; p < 0.001) and positively changed dietary intake (3.2 servings/week more of fruits and vegetables and 4.1 fewer of sugary drinks), physical activity (45.6 min/week more) and screen time (58.2 min/day less). Results from the control group showed no significant changes. Conclusion: Structured obesity prevention programs integrated into primary care improve early childhood health behaviors and weight trajectories substantially. Such interventions are feasible and have impact in resource constrained settings, as we show in these findings.